2011
DOI: 10.1097/qad.0b013e32834d0c20
|View full text |Cite
|
Sign up to set email alerts
|

Initial viral decay to assess the relative antiretroviral potency of protease inhibitor-sparing, nonnucleoside reverse transcriptase inhibitor-sparing, and nucleoside reverse transcriptase inhibitor-sparing regimens for first-line therapy of HIV infection

Abstract: Objectives To evaluate the effects of gender and initial antiretroviral regimen on decay of HIV RNA and virologic outcome. Methods We conducted a viral dynamics sub-study of A5142, a trial comparing lopinavir/ritonavir+efavirenz (LPV/EFV) versus LPV+2 NRTI (LPV) versus EFV+2 NRTI (EFV) in ARV-naive subjects. HIV RNA was measured at days 2, 10, and 14 in the sub-study and at weeks 1, 4, and 8 in A5142 participants. Two-phase viral decay was estimated in the sub-study with bi-exponential mixed-effects modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 24 publications
(25 reference statements)
5
40
1
Order By: Relevance
“…For instance, Haubrich et al [12] observed a greater viral decay in patients with pre-HAART viraemia >100,000 copies/ml than in those with pre-HAART viraemia <100,000 copies/ml after approximately 2 weeks of HAART. A potential explanation of this phenomenon is the presence of a larger infected cell population in patients with higher viraemia before starting treatment, predominantly done by longlived productively infected cells [12]. Whether this interesting result (with obvious therapeutic consequences) is driven by patients with very high viraemia (>500,000 copies/ml) or by all those with >100,000 copies/ml is not defined in that study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Haubrich et al [12] observed a greater viral decay in patients with pre-HAART viraemia >100,000 copies/ml than in those with pre-HAART viraemia <100,000 copies/ml after approximately 2 weeks of HAART. A potential explanation of this phenomenon is the presence of a larger infected cell population in patients with higher viraemia before starting treatment, predominantly done by longlived productively infected cells [12]. Whether this interesting result (with obvious therapeutic consequences) is driven by patients with very high viraemia (>500,000 copies/ml) or by all those with >100,000 copies/ml is not defined in that study.…”
Section: Discussionmentioning
confidence: 99%
“…The current definition of high viral load is >100,000 copies/ml, and nearly all studies, and guidelines, tend to adapt their analyses and statements to this threshold [2,6,12,[17][18][19][20][21]. For instance, Haubrich et al [12] observed a greater viral decay in patients with pre-HAART viraemia >100,000 copies/ml than in those with pre-HAART viraemia <100,000 copies/ml after approximately 2 weeks of HAART. A potential explanation of this phenomenon is the presence of a larger infected cell population in patients with higher viraemia before starting treatment, predominantly done by longlived productively infected cells [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since sCD30 decreases with decreasing HIV-1 pVL, it may be useful as an indicator for virological success during ART [8,10]. It is also known that early HIV-1 decay within one month of therapy can be predictive of long term outcomes [11][12][13]. However, it is unclear if sCD30 decline during the early stage of ART will be useful for predicting HIV-1 pVL suppression during this early phase of ART where immune reconstitution disease (IRD) and co-infections may be present [14].…”
Section: Introductionmentioning
confidence: 99%